Hubungan Pengetahuan Dan Dukungan Keluarga Terhadap Kunjungan Balita Ke Posyandu Di Desa Lahunggumbi Kecamatan Pondidaha - La Ode Liaumin Azim (Jurnal Praba : Jurnal Rumpun Kesehatan Umum, 2025)
Posyandu is one of the health facilities that plays an important role in monitoring the growth and development of toddlers, especially in rural areas. The number of infant visits to posyandu in Konawe District is still very low. In 2024, 25.6% of posyandu were classified as primary, 27.1% as intermediate, 43.9% as advanced, and 3.3% as independent. Visits by toddlers to Posyandu are influenced by various factors, including parental knowledge and family support. This study aims to determine the extent to which parental knowledge and family support influence the frequency of visits by toddlers to Posyandu in Lahunggumbi Village in 2025. This study uses an observational design with a cross-sectional approach. The research sample consisted of 35 parents of toddlers who were randomly selected from Lahunggumbi Village. Data collection was conducted through interviews using a questionnaire that had been tested for validity and reliability. The data obtained were analyzed using the chi-square statistical test to examine the relationship between parental knowledge and family support on infant visits to the Posyandu. The results showed that there was a significant relationship between parental knowledge (p = 0.015) and family support (p = 0.009) and the frequency of infant visits to the Posyandu. Parental knowledge and family support have a significant influence on infant visits to the Posyandu in Lahunggumbi Village. Therefore, inter